2009
DOI: 10.1158/1078-0432.ccr-08-1954
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Regulation of Bv8 in Human Blood Cells

Abstract: Purpose: Bv8, also known as prokineticin 2, has been recently shown to be a mediator of myeloid cell^dependent tumor angiogenesis in mouse models. We wished to determine whether these findings might be potentially relevant to human disease. Experimental Design: We characterized Bv8 expression in human blood cells in vitro and in vivo, and did Bv8 immunohistochemistry in human tumor sections. We also partially purified Bv8 from human neutrophils and tested its bioactivity. Results: We found that Bv8 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 51 publications
4
56
0
Order By: Relevance
“…Importantly, Bv8 upregulation in response to G-CSF (and GM-CSF) has been reported in human neutrophils (71). The immunohistochemical localization of Bv8 protein in human tumor-infiltrating neutrophils has also been reported (71). In a complementary fashion, neutrophils can also recruit Th17 cells to the inflammatory sites through secretion of CCL2 and CCL20 (72).…”
Section: Angiogenic Properties Of Tumor-associated Neutrophilsmentioning
confidence: 98%
See 2 more Smart Citations
“…Importantly, Bv8 upregulation in response to G-CSF (and GM-CSF) has been reported in human neutrophils (71). The immunohistochemical localization of Bv8 protein in human tumor-infiltrating neutrophils has also been reported (71). In a complementary fashion, neutrophils can also recruit Th17 cells to the inflammatory sites through secretion of CCL2 and CCL20 (72).…”
Section: Angiogenic Properties Of Tumor-associated Neutrophilsmentioning
confidence: 98%
“…Blockade of IL17/IL17 receptor, G-CSF/G-CSF receptor, or Bv8-through genetic and pharmacologic approaches-inhibits intratumoral infiltration of neutrophils, tumor angiogenesis, and tumor growth (38,39,68). Importantly, Bv8 upregulation in response to G-CSF (and GM-CSF) has been reported in human neutrophils (71). The immunohistochemical localization of Bv8 protein in human tumor-infiltrating neutrophils has also been reported (71).…”
Section: Angiogenic Properties Of Tumor-associated Neutrophilsmentioning
confidence: 99%
See 1 more Smart Citation
“…S12C). Bv8 has been shown to promote migration of myeloid cells (31). Therefore, we considered the possibility that Bv8 might also promote migration of metastatic tumor cells.…”
Section: G-csf Induces Expression Of Several Prometastatic Moleculesmentioning
confidence: 99%
“…PROK2 is a chemokine with five disulfide bonds and was shown to be expressed in inflamed tissues (17). It was observed that the secretion of PROK2 from lymphocytes stimulate IL-10 and this process causes an increase in angiogenesis (18). An increase in PROK2 may play a role in BD neoangiogenesis with a vascular pattern.…”
Section: Discussionmentioning
confidence: 99%